Investment in reward by ant-dispersed plants consistently selects for better partners along a geographic gradient. Issue 3 (2nd May 2019) - Levine, Nataly; Ben-Zvi, Gilad; Seifan, Merav; Giladi, Itamar
Abstract: Seed dispersal by ants (myrmecochory) is an asymmetric, presumably mutualistic interaction, where a few ant species benefit many plants. Myrmecochorous plants express specialized adaptations, most notably a large elaiosome, which promote interactions with efficient seed dispersers while decreasing interactions with poor dispersers, resulting in de facto partner choice. However, because variation in plants' investment in reward and ant response to them may vary spatially and temporally, it is unclear whether such specialization is consistent along geographic gradients; especially towards myrmecochory's range margin. To answer this question on context-dependent partner choice, we first estimated variation in reward investment by co-occurring myrmecochores along a steep environmental gradient in a Mediterranean region. Second, we tested whether variation in plant investment in reward was positively and consistently correlated with the quality of dispersal plant received along the same gradient. Using in situ cafeteria experiments, we simultaneously presented diaspores of locally co-occurring myrmecochorous species to ants of two guilds representing high- and low-quality dispersers. We then recorded ant-seed behaviour, seed preference and seed removal rates for each ant guild. We found both overall and within-site high variation among plant species in the total and relative investment in elaiosomes. Both ant guilds removed substantial proportion of the seeds. However, scavenging ants (high-quality dispersers) clearly preferred diaspores with larger elaiosomes, whereas granivorous ants (low-quality dispersers) exhibited no preference. Furthermore, both the variation in plant traits and the corresponding response of different ant guilds were consistent along the studied geographic gradient. This consistency holds even when granivores, which removed seeds in a non-selective fashion and provided apparently low-quality seed dispersal services, were, at least numerically, the dominant ant guild. This dominance and the consistency of the partner choice shed light on the functionality of elaiosomes at the margins of myrmecochory's distribution. Abstract : Seed dispersal by ants is a mutualistic interaction in which some ants disperse the seeds of plants, which produce a lipid-rich seed appendage that serves as a reward to the ants. The strength of this interaction varies with the quality of the reward, by the quality of dispersal provided by the ants and by the environmental context. We found that, among co-occurring plant species, those that produced larger rewards were preferred by high-, but not by low-quality seed-dispersing ant species. This preference pattern was consistent along a sharp geographic gradient in a Mediterranean ecosystem.